Impact of Accounting Intelligence System on Corporate Performance: Evidence from Selected SMEs in Nigeria - Shehu, Titilayo Silifat (New Ideas Concerning Arts and Social Studies Vol. 3, 2025)
Accounting intelligence systems (AIS) have become indispensable tools for firms aiming to improve financial accuracy, reduce human errors, and provide timely hints for strategic decisions. The study examines the impact of Accounting Intelligence Systems, specifically decision support systems (DSS) and executive support systems (ESS), on the corporate performance of SMEs in Nigeria. Using a descriptive survey design, data were collected from 196 owners, managers, and financial officers through structured questionnaires. Multiple regression analysis revealed that both DSS and ESS significantly influence SME performance, with ESS having a stronger effect. The findings suggest that adopting modern financial information systems can enhance decision-making, operational efficiency, and competitiveness among Nigerian SMEs. The study highlights the need for SMEs to invest in integrated financial systems to promote sustainable growth.